CHORIOCAPILLARIS FLOW IMPAIRMENT IN TYPE 3 MACULAR NEOVASCULARIZATION: A Quantitative Analysis Using Swept-Source Optical Coherence Tomography Angiography. Issue 9 (September 2021) - Le, Hoang Mai; Souied, Eric H.; Querques, Giuseppe; Colantuono, Donato; Borrelli, Enrico; Sacconi, Riccardo; Amoroso, Francesca; Capuano, Vittorio; Jung, Camille; Miere, Alexandra
Abstract : Purpose: To quantitatively analyze choriocapillaris alterations using swept-source optical coherence tomography angiography in eyes presenting with Type 3 macular neovascularization (MNV) and to compare these alterations with eyes presenting with intermediate AMD (iAMD). Methods: Macular 3 × 3-mm swept-source optical coherence tomography angiography scans were retrospectively analyzed in eyes with Type 3 MNV and in eyes with iAMD. The choriocapillaris en face slabs were extracted from the swept-source optical coherence tomography angiography device after manual segmentation. En face choriocapillaris flow images were compensated with en face choriocapillaris structure images, followed by the Phansalkar local thresholding method using a window radius of 4 and 8 pixels. The percentage of flow deficits (FD%), the number, size, and total area of FDs were computed for comparison. A secondary analysis was performed in the four corners of the image to include equidistant regions in all eyes. Results: Twenty-six Type 3 MNV eyes of 21 patients and 26 iAMD eyes of 17 patients were included. Compared with iAMD eyes, eyes with Type 3 MNV displayed a higher FD% (41.37% ± 14.74 vs. 19.80% ± 9.63 using radius 4 pixels [ P < 0.001]; 45.24% ± 11.9 vs. 26.63% ± 8.96 using radius 8 pixels [ P < 0.001]). The average size of FDs was significantly larger in Type 3 MNV eyes compared with iAMD eyes ( P < 0.001), whereas the number of FDs was significantly lower in Type 3 MNV compared with iAMD eyes ( P < 0.001). Conclusion: Type 3 MNV eyes present with increased choriocapillaris flow impairment compared with iAMD eyes. Reduced choriocapillaris perfusion may contribute to Type 3 MNV development and pathogenesis. Abstract : Quantitative analysis of the choriocapillaris flow using swept-source optical coherence tomography angiography shows that eyes presenting with Type 3 macular neovascularization present a decreased choriocapillaris perfusion compared with intermediate age-related macular degeneration eyes, with the percentage of flow deficits, total area, and average size of flow deficits greater than intermediate age-related macular degeneration eyes.